Program KKN-T Sebagai Wujud Pengabdian Masyarakat: Peningkatan Kesadaran Kebersihan Lingkungan Perumahan Al-Fayyadh - Juliana, Pinti; Wulandari, Annisa; Siboro, Nadia Sauli Yanti BR.; Pirdayanti, Mei Sela; Aprilia, Dela; Nasution, Suswati; Soleh, Ahmad; Gayatri, Ida Ayu Made Er Meytha (Universitas Dehasen Bengkulu, 2025)
The Thematic Community Service Program (KKN-T) emphasizing environmental cleanliness awareness enhancement has been implemented in Al-Fayyadh Housing Complex, RT 23 RW 04, Pematang Gubernur Village, Muara Bangka Hulu District, Bengkulu City. The main objective of this program is to increase awareness and active participation of the community in maintaining residential environmental cleanliness as a form of community service. The program implementation method employs a comprehensive approach, including socialization activities to provide theoretical understanding, counseling to enhance residents' knowledge, and community service activities as practical implementation. This approach is designed to encourage direct community involvement in maintaining environmental cleanliness.The program evaluation results demonstrate significant positive impact, with residents' awareness regarding the importance of environmental cleanliness increasing by 75% and participation in community service activities increasing by 60%. This program successfully created tangible changes by establishing a clean, healthy, and comfortable residential environment for all communities. The success of this program shows that participatory and educational approaches can be effective strategies in enhancing environmental awareness among communities.